Legal Reformulation of Political Rights of Members of the Indonesian National Army to Ensure Democratic Justice and Enforcement of Human Rights - Ferdinal, Ocktave; Israhadi, Evita Isretno (Jurnal Greenation Sosial dan Politik, 2025)
Political rights, including the right to vote, are fundamental components of human rights as enshrined in the 1945 Constitution of the Republic of Indonesia—specifically Article 27(1), Article 28D(1), and Article 28E(3)—and further reinforced by Article 43 of Law No. 39 of 1999 concerning Human Rights. These constitutional provisions are consistent with Article 21 of the Universal Declaration of Human Rights, which affirms that “Everyone has the right to take part in the government of his country, directly or through freely chosen representatives.” In practice, however, statutory provisions such as Article 39 of Law No. 34 of 2004 on the Indonesian National Army and Article 200 of Law No. 7 of 2017 on Elections explicitly prohibit members of the Indonesian National Army from exercising their right to vote. This raises concerns regarding legal coherence and potential breaches of the principle of non-discrimination. This research examines the legal-political framework regulating the political rights of military personnel and proposes a legal reformulation grounded in the principles of human rights and equitable democratic participation. Employing a normative legal methodology, the study adopts statutory and conceptual approaches informed by the notion of non-discriminatory justice. The findings highlight inconsistencies between current legal norms and constitutional values, advocating for a phased legal reform which distinguishes between active and passive suffrage, supported by independent oversight to uphold military neutrality without infringing upon the constitutional rights of citizens.